PENGARUH GAYA KEPEMIMPINAN DEMOKRATIS TERHADAP KINERJA KARYAWAN DENGAN MOTIVASI KERJA SEBAGAI VARIABEL ANTARA - Firmansyah, Deni; Winarto, Jacinta (FEB Universitas Sam Ratulangi Manado, 2024)
This study's goal was to ascertain and examine how democratic leadership styles affect worker performance, using work motivation as an intermediate variable. The research sample for this study consisted of 33 staff members from the Faculty of Medicine, Maranatha Christian University, using nonprobability sampling as the sampling strategy. Likert scale was included in the questionnaire utilized as the data gathering method. Because the research uses a limited sample size, the data processing approach used is Structural Equation Model - Partial Least Square (SEM-PLS). The findings of this study demonstrate that: democratic leadership style has no effect on worker performance, democratic leadership style has a positive and significant effect on worker motivation, work motivation has a positive and significant effect on employee performance, and democratic leadership style has a positive and significant effect on employee performance with work motivation as an intermediate variable.